LO26: The efficacy of high dose cephalexin in the outpatient management of moderate cellulitis for pediatric patients. (15th May 2017) - Farley St-Amand, B.; Trottier, E. D.; Autmizguine, J.; Vincent, M.; Tremblay, S.; Chevalier, I.; Gouin, S.
Abstract : Introduction: Children with moderate cellulitis are often treated with IV antibiotics in the hospital setting, as per recommendations. Previously in our hospital, a protocol using daily IV ceftriaxone with follow-up at the day treatment center (DTC) was used to avoid admission. In 2013, a new protocol was implanted and suggested the use of high dose (HD) oral cephalexin with follow-up at the DTC for those patients. The aim of this study was to evaluate the safety and efficacy of the HD cephalexin protocol to treat moderate cellulitis in children as outpatient.Methods: A retrospective chart review was conducted. Children were included if they presented to the ED between January 2014 and 2016 and were diagnosed with a moderate cellulitis sufficiently severe to request a follow up at DTC and who were treated according to the standard of care with the HD oral cephalexin (100 mg/kg/day) protocol. Descriptive statistics for clinical characteristics of patients upon presentation, as well as for treatment characteristics in the ED and DTC were analyzed. Treatment failure was defined as: need for admission at the time of DTC evaluation, change for IV treatment in DTC or return visit to the ED. Outcomes were compared to historic controls treated with IV ceftriaxone at the DTC, where admission was avoided in 80% of cases.Results: During the study period, 682 children with cellulitis were diagnosed in our ED. Of these, 117 patients were treated using the oral HD cephalexin outpatient protocol. Success rate was 89.5% (102/114); 3 patients had an alternative diagnosis at DTC. Treatment failure was reported in 12 cases; 10 patients (8.8%) required admission, one (0.9%) received IV antibiotics at DTC, and one (0.9%) had a return visit to the ED without admission or change to the treatment. This compares favorably with the previous study using IV ceftriaxone (success rate of 80%). No severe deep infections were reported or missed; 4 patients required drainage. The mean number of visits per patient required at the DTC was 1.6.Conclusion: Treatment of moderate cellulitis requiring a follow-up in a DTC, using an oral outpatient protocol with HD cephalexin is a secure and effective option. By reducing hospitalization rate and avoiding the need for painful IV insertion, HD cephalexin is a favourable option in the management of moderate cellulitis for pediatric patients, when no criteria of toxicity are present.